Pengembangan Aplikasi Pemesanan Makanan Berbasis Web Mobile Menggunakan Metode Prototyping pada KAF Fried Chicken - Muhammad Taufik Ridho; Hidayat, Ahmad Tri (Universitas Putra Indonesia YPTK Padang, 2024)
The development of information and communication technology has brought significant changes in various aspects of life, including in terms of ordering food. The design of a food ordering application at the KAF Chicken outlet is very necessary to reduce the constraints of conventional systems. The problem commonly faced by various culinary businesses is the absence of an automated system to record and manage orders, customer data, and financial reports, which often results in inaccuracy and slows down the process. This study aims to design a mobile web-based food ordering application that can facilitate culinary business management in ordering, payment, and transaction data management. The application uses the spiral method that allows gradual development and uses the Express Js Framework and Mongodb as data management. Application features include menu management, online ordering, and transaction recording. Based on the test results, this system can help control transaction data and manage reports accurately and quickly. The design of this application can also be expected to contribute positively to improving the operational efficiency of the culinary business, especially in managing orders and transaction data.